First case of an infection of the metacercariae of Austrodiplostomum compactum (Lutz, 1928) (Digenea, Diplostomidae) in Hypostomus regani (Ihering, 1905) (Siluriformes: Loricariidae). - Zica, Erica O.P.; Santos, Karina R.; Ramos, Igor P.; Zanatta, Augusto S.; Carvalho, Edmir Daniel [UNESP]; Silva, Reinaldo J. (My University, 2009)
Austrodiplostomum compactum (Lutz, 1928) (Digenea, Diplostomidae) was recorded infecting the eyes of a Hypostomus regani (Ihering, 1905) (Siluriformes: Loricariidae). This is the first report of a loricarid fish infected with A. compactum.